The convergent chemical synthesis of histone H3 protein for site-specific acetylation at Lys56 and ubiquitination at Lys122. Issue 29 (29th March 2017) - Qi, Yun-Kun; He, Qiao-Qiao; Ai, Hua-Song; Guo, Jing; Li, Jia-Bin
Abstract : The first total chemical synthesis of modified H3 bearing Lys56 acetylation and Lys122 ubiquitination. Abstract : Deposition of (H3–H4)2 tetramers is believed to be the critical step in nucleosome assembly. Site-specific acetylation and ubiquitination of histone H3 have been speculated to synergistically facilitate the formation and deposition of (H3–H4)2 tetramers. Here we report our endeavors toward the first chemical synthesis of homogenous histone H3, which bears Lys56 acetylation and Lys122 ubiquitination, for in vitro biochemical and biophysical studies.